(untitled) (Global Journal of Management and Business Research, 2021)
This theoretical documentary non-experimental and descriptive research analyzes the trends in the development of the digital economy In this document it is possible to identify what aspects such as digital payments cyber security and electronic commerce are fundamental factors in developing an increasingly digitized economy This process that has accelerated after the coronavirus pandemic as of 2020 Specifically the document shows statistics and data of Mexico regarding online sales and the use of digital payment systems This document contributes to the study and analysis of the factors that influence the development of the digitization of the economy